2007
DOI: 10.1103/physrevb.76.184521
|View full text |Cite
|
Sign up to set email alerts
|

s-wave superconductivity phase diagram in the inhomogeneous two-dimensional attractive Hubbard model

Abstract: We study s-wave superconductivity in the two-dimensional square lattice attractive Hubbard Hamiltonian for various inhomogeneous patterns of interacting sites. Using the Bogoliubov-de Gennes (BdG) mean field approximation, we obtain the phase diagram for inhomogeneous patterns in which the on-site attractive interaction Ui between the electrons takes on two values, Ui = 0 and −U/(1 − f ) (with f the concentration of non-interacting sites) as a function of average electron occupation per site n, and study the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 65 publications
(117 reference statements)
0
12
0
Order By: Relevance
“…55,56 It was shown that an exponentially decaying subgap density of states appears due to mesoscopic fluctuations which lie beyond the mean-field picture. Finally, inhomogeneous couplings in the attractive Hubbard model 57,58 and lattice XY model 59 were also analyzed, with relevance to high-T c materials.…”
Section: Introductionmentioning
confidence: 99%
“…55,56 It was shown that an exponentially decaying subgap density of states appears due to mesoscopic fluctuations which lie beyond the mean-field picture. Finally, inhomogeneous couplings in the attractive Hubbard model 57,58 and lattice XY model 59 were also analyzed, with relevance to high-T c materials.…”
Section: Introductionmentioning
confidence: 99%
“…As U increases, going into the strong coupling limit region (U=tb1), z seems to stabilize in a specific value. This feature appears also in s-wave superconductors in the inhomogeneous twodimensional attractive Hubbard model [12]. In fact, in some materials z seems to have a constant value.…”
Section: Numerical Results and Conclusionmentioning
confidence: 95%
“…For these systems and phenomena, models like the repulsive Hubbard or t-J Hamiltonians are essential. Nevertheless, it is yet beneficial to study the problem first by employing a simpler and more phenomenological model [26]. Hence we propose a very simple model taking s-wave symmetry in one dimension for the study of gaps as follows.…”
Section: Theoretical Model and Calculationsmentioning
confidence: 99%